Dynamics of Physical Development and Physical Fitness of Fresh-Year Students Depending on the Sports Orientation of the Educational and Training Process - Turdimuratov Jengis Auezovich; Kuralbaev Azizbek Kuralbaevich; Djanxojaev Nurlan Djanuzakovich (Zien Journals, 2024)
The article presents the results of pedagogical experiments to study the influence of value motives for physical exercise on the health status of students in the process of physical education. Based on this, it becomes possible to determine the lagging link (physical quality) and identify the main training strategy characteristic of this group of students, because One of the tasks of physical education of students is the diversified development of physical qualities.
Keywords: Physical culture; dynamics; values; motives